Regulation of peptide‐chain elongation in mammalian cells - Browne, Gareth J.; Proud, Christopher G. (European journal of biochemistry, 2002)
The elongation phase of mRNA translation is the stage at which the polypeptide is assembled and requires a substantial amount of metabolic energy. Translation elongation in mammals requires a set of nonribosomal proteins called eukaryotic elongation actors or eEFs. Several of these proteins are subject to phosphorylation in mammalian cells, including the factors eEF1A and eEF1B that are involved in recruitment of amino acyl‐tRNAs to the ribosome. eEF2, which mediates ribosomal translocation, is also phosphorylated and this inhibits its activity. The kinase acting on eEF2 is an unusual and specific one, whose activity is dependent on calcium ions and calmodulin. Recent work has shown that the activity of eEF2 kinase is regulated by MAP kinase signalling and by the nutrient‐sensitive mTOR signalling pathway, which serve to activate eEF2 in response to mitogenic or hormonal stimuli. Conversely, eEF2 is inactivated by phosphorylation in response to stimuli that increase energy demand or reduce its supply. This likely serves to slow down protein synthesis and thus conserve energy under such circumstances.